What is the physical condition profile of elderly women? Research looking at the level of flexibility - Mohamad Dai; Febriyan Dwi Cahyono; Devi Lestya Pembayun (Universitas Tanjungpura, 2024)
Background and Study Aim. Age changes are believed to be one of the factors affecting a person's physical abilities. Decreased physical capacity will result in some direct interference in doing everyday activities. The research has made important contributions to the field of health and fitness of the elderly by providing empirical data on the physical condition and flexibility abilities of older women. Material and Methods. The research uses observational and cross-sectional designs. The sample in this study was 17 elderly women aged over 60. Data collection techniques use body height measurements using stadium meters, weight using digital scales and sit and reach to measure flexibility capabilities. Data analysis using the SPSS 22 application. Results. The results showed that the Body Time Index value of 21.6 was in the ideal category and flexibility ability had a value of 11.4 Cm which was in the good category. The findings of this study suggest that despite their old age, most subjects of the study have an ideal IMT and good flexibility, which is a positive indicator of their physical health. Conclusion. This data can be used by health professionals and fitness professionals to create more effective and targeted support programmes, as well as as an initial evaluation of the ability to monitor the progress of a fitness program.